Development of Animated Video Media Using Powtoon Application to Improve the Fourth-Grade Elementary Students’ Motivation in Learning - Indah Romasari Hutapea; Patri Janson Silaban; Dyan Wulan Sari HS; Bogor Lumban Raja; Saut Mahulae (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This paper examines the development, feasibility, and response of students about animated video media using the Powtoon application in order to increase students’ learning motivation in theme 8 of My Living Area on Subtheme 1 of My Living Environment Learning 1 in Class IV SD ST. Antonius Bangun Mulia Medan. The research is a research and development using the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The research subjects are four validators, namely one validator of learning media design experts, two experts in learning media materials, and one education practitioner who is carried out by class teachers. The sample consists of 30 students. Data collection techniques are tests, questionnaires, and documentation. Based on data analysis, it is concluded that animated video media using the Powtoon application to increase students’ motivation in learning result is